Boss payroll management system / Ong Siew Kheng - Ong , Siew Kheng (2004)
YTL Power Services is a multi-disciplinary services company registered in Malaysia, specializing in the operation and maintenance of power stations. The enterprise is jointly owned by YTL Corporation Berhad and Siemens AG of Germany up to the end of 200 l. From 2002 the company ownership is l 00% YTL Corporation. The company had its origins in Malaysia's newly competitive power industry, which was transformed in the early I 990's by privatisation and the arrival of independent power producers. The company manages the entire range of operation and maintenance (O&M) activities for YTL Power's two Malaysian power station s, which together generate about 12% of the electricity consumed in Peninsular Malaysia. YTL Power Services also provides engineering expertise to other projects in the region. Technology transfer is built into the structure of the company and has been the guiding philosophy behind its formation and growth. YTL Power Services is a modern company operating in a high-technology environment and the use of the latest equipment and techniques for maintaining and running combined cycle gas turbine power plants is integral to the company' organization. The primary objective of YTL Power Service: to develop a sustainable payroll management system in Human Resource Department due to Increasing of employee in the organization. The current database is using Microsoft Access 97 to update and controlling employee data for the total of 314 employees was facing difficulties where the backup is not sufficient enough to track the back record.